UTILIZING CANVA IN INTERACTIVE LEARNING MEDIA ON THE LEARNING INTEREST OF GRADE 4 STUDENTS OF SD NEGERI 8 MAMBORO - Wahyuni; Rizal; Kalsum Hiola (EDU RESEARCH, 2024)
This research aims to determine the use of Canva in interactive learning media on students' interest in learning at SD Negeri 8 Mamboro. This type of research is classroom action research (PTK). This research consisted of 3 cycles. Cycle 1 involves planning, action, observation, reflection or evaluation in interactive learning in the classroom. The data obtained is from observations, and interviews or questions and answers related to students' understanding of the material presented. The tools and materials used in this research are laptops, infocus, and PPT media which have been created using the Canva application. Meanwhile, the sample in this study was Class IVA students at SD Negeri 8 Mamboro, with a total of 19 students consisting of 11 female students and 8 male students. The research results show that the percentage of success results is that an average of 79% of students understand the concept of the material so they are included in the good category and an average of 81% of students have very good learning outcomes. So it can be concluded that it is included in the maximum category for students' learning interest.